ANALISIS ALTMAN Z''-SCORE SEBAGAI ALAT EARLY WARNING SYSTEM RISIKO FINANCIAL DISTRESS STUDI KASUS PT WASKITA KARYA (PERSERO) TBK - Murviana Koto; Ikhsan Abdullah (CERED Indonesia Institute, 2026)
This study examines the level of financial distress risk at PT Waskita Karya (Persero) Tbk over the 2021–2024 period using the Altman Z''-Score model as an early warning system within the framework of financial risk management. The study is motivated by the persistent financial pressure faced by state-owned construction companies, characterized by high leverage, limited liquidity, and heavy reliance on long-term debt financing. Secondary data are obtained from audited consolidated financial statements and analyzed using a descriptive quantitative approach with a longitudinal case study design. The findings reveal that although the Z''-Score values demonstrate a gradual improving trend throughout the observation period, the company consistently remains within the distress zone, indicating a sustained and elevated risk of bankruptcy. These results confirm the effectiveness of the Altman Z''-Score model as an early warning tool for identifying financial risk and provide important implications for managerial decision-making and financial restructuring policies, particularly for highly leveraged construction firms operating in emerging markets.